PENGARUH ECO-ENZYME DAN BIOCHAR SEKAM PADI TERHADAP PERTUMBUHAN BIBIT TANAMAN CENGKEH (Syzygium aromaticum L.) PADA MEDIA PODSOLIK MERAH KUNING - Frendy Maulana Ichsan; Sulhaswardi (UIR Press, 2024)
This study investigates the combined effects of Eco-Enzyme and Rice Husk Biochar on the growth of Clove Plant Seedlings (Syzygium aromaticum L.) in red and yellow podsolic media. Conducted at the experimental farm of the Faculty of Agriculture at the Islamic University of Riau, the research spanned four months, from January to April 2024. The study employed a Factorial Complete Random Design (RAL) with two factors: the application of Eco-Enzyme (factor Z) at five levels—0 ml, 10 ml/l water, 20 ml/l water, 30 ml/l water, and 40 ml/l water—and Rice Husk Biochar (factor B) at four levels—0 g, 100 g/polybag, 200 g/polybag, and 300 g/polybag. The parameters observed included plant height, leaf count, chlorophyll content, stomatal number, stem base diameter, longest root length, root volume, crown fresh weight, and root-to-crown ratio. The results indicated that the interaction between Eco-Enzyme and Rice Husk Biochar significantly influenced plant height, leaf count, chlorophyll levels, stomatal numbers, stem base diameter, root length, crown fresh weight, and the root-to-crown ratio. The best treatment was identified as an Eco-Enzyme concentration of 40 ml/l water combined with 300 g of rice husk biochar per polybag (Z4B3). Eco-Enzyme had a significant main effect on all parameters, with the optimal treatment being 40 ml/l water. Similarly, Rice Husk Biochar also had a significant main effect on all observed parameters, with the best treatment being 300 g/polybag.